PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI 2 DIMENSI MATA PELAJARAN AGAMA HINDU MENGENAI SAD RIPU STUDI KASUS KELAS VI (ENAM) SD NEGERI 1 KALIBUKBUK - Ekaputra, Putu Wisnu; Sindu, I Gede Partha; Suyasa, P Wayan Arta (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to determine (1) the design and impementation of the development of a 2-dimentional animation learning video for sad ripu of hindu religion subject for 6th grade at SD Negeri 1 Kalibukbuk. The result of 6th grade response shows that 2-dimentional animation learning video is suitable for learning media of sad ripu of hindu religion subject. Research method used for the development is MDLC (Multimedia Development Life Cycle) approach which contained several steps, they are concept, design, material collecting, assembly, testing, and distribution. Study result shows that the elementary student as user of the learning video gave positive response and very enthusiastic about learning sad ripu of hindu religion subject with learning video. (2) From the result of response test to 10 elementary student as respondent to see the feasibility of learning video obtained result of 85%, which means 2-dimentional animation learning video for sad ripu of hindu religion subject is included in the good category.Â Keywords: Learning Video, 2D Animation, Hinduism, Sad Ripu, MDLC (Multimedia Development Life Cycle).